Ukraine - The Financial Sector and the Economy : The New Policy Agenda - Roe, Alan; Forgacs, Katalin; Olenchyk, Andriy; Peachey, Stephen; Prigozhina, Angela; Vlasenko, Yuri; Zhyliaev, Ihor (Washington, DC: World Bank, 2013)
This report provides an up-dated assessment of the situation in Ukraine's financial sector (banks as well as non-banks) and defines a policy agenda for the next stages of reform. The report is addressed to those in authority in Ukraine who have influence over the future development of the sector. The report updates a 1995 report prepared by the Bank that has served as the framework for much of the Bank's involvement with the sector in the intervening six years, and has also been a significant influence on the government's own reform efforts in the sector. This report looks in detail at a sub-set of the necessary policy reforms. Some other matters such as deregulation and the detailed proposals regarding banking supervision have been the subject of other detailed Bank and International Monetary Fund (IMF) reports and so are not considered here. The remainder of this Policy Report is organized as follows. Section two has two main purposes. The first is to identify the main elements in the recent performance of the real economy that have complicated the task of developing a stronger financial sector. The second is to identify the various ways in which the financial sector is failing to make as large a contribution as it could to the economy's recovery and future growth. Annexes one and two provide further elaboration. Section three sets out the basic framework for designing the reform agenda for the banking component of the sector. Section four provides a forward looking perspective of what might realistically be expected by way of new financing for the economy through the period to 2005 in the event that a sustained reform effort is now adopted. Section five looks in more depth at the banking sector and analyses the size and nature of the reforms in individual classes of banks especially the larger ones that will be needed to realize the stronger future performance for the sector as set out in section four. Section six provides a similar in-depth analysis of the situation of the nonbank financial institutions, including some whose activities interact very directly with the capital market institutions. Section seven defines the integrated reform strategy for the sector which emerges from the analysis in the report and related reports by others.